High thermochromic performance of Fe/Mg co-doped VO2 thin films for smart window applications. Issue 24 (7th June 2018) - Ji, Chunhui; Wu, Zhiming; Lu, Lulu; Wu, Xuefei; Wang, Jun; Liu, Xianchao; Zhou, Hongxi; Huang, Zehua; Gou, Jun; Jiang, Yadong
Abstract : A new method, Fe/Mg co-doping, is proposed for the first time to optimize thermochromic VO2 and the promising performance of VO2 -based smart windows for practical applications is successfully achieved. Abstract : In the field of energy-efficient smart windows, vanadium dioxide (VO2 ) is a promising material due to its reversible metal–insulator transition. However, the development of VO2 -based smart windows has been restricted by several drawbacks in performance, including high phase transition temperature ( T C ), low luminous transmittance ( T lum ), insufficient solar energy modulation ability (Δ T sol ) and unpopular color. In this paper, Fe/Mg co-doping is proposed for the first time to improve the thermochromic performance of VO2 films. Interestingly, the Fe/Mg co-doped films can exhibit outstanding thermochromic performance with a balanced solar regulation efficiency of 12.8%, suitable luminous transmittance up to 42.1%, and low phase transition temperature around 38.2 °C, which is very promising for practical applications. In addition, the color of films is modified to increase their brightness and lighten the brown color. Different from previous work on co-doped VO2 focusing on W 6+ and low-valence (<4+) elements, Fe 3+ /Mg 2+ co-doping is found to have the synergistic combination of the advantages of single doping with Fe and Mg by getting rid of the neutralization between charge carriers e − and h + . Such a feature is especially desired for optimizing the thermochromic performance with co-doping methods. This study provides a new solution for improving the optical properties of VO2 films for smart window applications.